Conditional Effects of Consumer-Brand Relationships on Admired and Non-Admired Brands, and Its Impact on Schadenfreude - Cucato; J.D.S.T, Strehlau; S., Strehlau; V.I., Bizarrias; S., Flávio (British Journal of Marketing Studies, 2023)
Extant literature on schadenfreude, a pleasure towards the misfortune of others, is concentrated on brand rivalry however is silent about situations when one own brand causes the schadenfreude. We advance knowledge on brand relationship by investigating how one brand’s bad malicious strategy leads to schadenfreude for admired and non-admired brands and is mitigated when admired brands interact with positive feelings elicited by brand-consumer relationship to protect against their own bad behavior. Firstly, we showed the phenomenon, then we point out the exact regions of moderation. The first study shows that schadenfreude is greater when the misfortune is due to a controlled action of the brand. The second study tests the mitigating effect of congruence between brand and Self. Study three tests higher-order affective levels such as brand love, as a negative moderating construct. Study four advances previous studies on consumers’ self-promoting feelings and their interaction with brands to produce schadenfreude.